Current Causes and Clinical Pattern of Fixed Drug Eruption at a Tertiary Care Hospital - Habib, Aamir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To identify the current common causative drugs and the clinical pattern of FDE in Pakistani patients presenting to a Tertiary Care Hospital. Study Design: Cross-sectional study. Place and Duration of Study: Department of Dermatology Combined Military Hospital, Kharian Pakistan, from Nov 2018 to Oct 2021. Methodology: Patients of all ages and sexes reporting in dermatology outpatient during the study period with Fixed drug eruption (FDE) were included in the study after taking informed consent. Diagnosis of FDE was based on the finding of welldemarcated erythematous patches or plaques and violaceous pigmentation. In cases where history was not suggestive, the drug was confirmed by an oral provocation test. In addition, the causative drug, site(s) affected, duration, number of skin lesions, history of FDE, and the purpose for using the drug were noted for each patient. Results: Sixty-one patients were included in the study. Doxycycline (thirteen patients, 21.3%) was the commonest causative drug, followed by Quinolones and Paracetamol in ten (16.4%) patients each, Cotrimoxazole in eight (13.1%) patients and Nonsteroidal anti-inflammatory drugs (NSAIDs) in seven (11.5%) patients. Multiple lesions were common in patients with a history of FDE. The disease affected single-body sites in 16(26.23%) patients only. The most common site was the genital area in forty-two (71.19%) patients, followed by upper limbs in thirty-one (52.54%) patients and lips in twenty-eight ............... Conclusions: Knowing the current causative drugs and carefully seeking a history of FDE may help prevent recurrent FDE.